Diagnosing an Acute Leukemia From a Necrotizing Ulcerative Gingivitis in The Oral Cavity: a Case Report - Andriani, Dwi; Hermawan, Panky (Odonto : Dental Journal, 2023)
Background: Necrotizing ulcerative gingivitis (NUG) is an acute onset of gingival disease, that presents as an acute, painful, and destructive ulceration and inflammation of gingival tissue. This condition is one of the oral manifestations of leukemia in addition to gingival enlargement and spontaneous bleeding, oral ulceration, petechiae, hematoma, and pale mucosa. Case Report: We reported A 50-year-old woman presented with gum swelling, pain, and easy bleeding in the lower jaw gums. The patient often experiences fatigue, spontaneous bruising, dry skin, and hair loss. Extraoral examination revealed bruises on the hand. Intraoral examination revealed swelling, erythematous and ulcerative lesion, tartar, bleeding on probing in the lingual gingiva of lower central incisor teeth, mucosa pallor, and minor petechiae were observed at the buccal mucosa region 47-48. The provisional diagnosis was NUG with suspicion of systemic disorder. Result: A complete blood count was performed which showed anemia, leukopenia, neutropenia, lymphocytosis, and thrombocytopenia. We diagnosed NUG in acute leukemia patients. Conclusion: This case demonstrates the detection of leukemia and its oral manifestations in acute leukemia patient. The patient was referred to the hematologist oncology.